Impact of Fundamental Factors on Stock Prices of Nepalese Commercial Banks - Thapa, Bhim Kumar (International Research Journal of MMC, 2026)
Purpose: This study investigates the relationship between key financial performance indicators and the market price per share (MPS) of commercial banks listed on the Nepal Stock Exchange (NEPSE). Against the backdrop of increasing investor interest and stock market volatility, the research aims to identify the determinants that significantly influence share valuation in Nepal’s banking sector. Methods: Using a positivist research philosophy, the study employed a quantitative approach and utilizes secondary data from all 19 commercial banks listed in NEPSE over a selected 2015 to 2024 years financial period. Data were extracted from official bank websites, NEPSE reports, and regulatory disclosures. The strength and direction of the association between independent variables, fundamental factors and MPS, were determined using descriptive statistics, Pearson correlation analysis, and multiple linear regression modeling. Findings: The findings revealed that book value per share (BVPS) and return on equity (ROE) were positively and significantly associated with MPS, indicating that stronger asset backing and profitability enhanced investor valuation. Dividend per share (DPS) also showed a positive effect but was less statistically significant. The regression model satisfied key assumptions of linearity, normality, and homoscedasticity was confirmed through residual diagnostics including studentized deleted residuals, Cook’s distance, leverage values, and visual plots. Conclusion: The study concludes that key financial indicators, particularly DPS, ROE, BVPS, and firm size, significantly influence the market price per share of listed firms. The findings validate major financial theories such as Signaling Theory, Residual Income Valuation Theory, Agency Theory, and Economies of Scale Theory in explaining stock price behavior. Implications: This study recommends to the policymakers and financial institutions promote transparent and consistent financial reporting, particularly around profitability and equity strength, to enhance market efficiency. Investors are advised to consider long-term performance indicators such as ROE and BVPS in portfolio decisions. Keywords: Book value per share, Dividend per share, financial performance indicators, Market price per share, Return on equity